Israel in the Biblical period : institutions, festivals, ceremonies, rituals - Soggin, J. Alberto (T & T Clark, 2001)
In this short, accessible and readable book, Professor Soggin gives an account of all the features of Israelite and Jewish religion in the biblical period. After a radical assessment of the nature of the sources and the problems of using them historically, he discusses the origin of monotheism and Israel''s belief in its one God Yahweh. Then follow accounts of the three most important features in Israelite religion: the Jerusalem temple and its worship, the covenant, and sacrifices. The main festivals are discussed and there are chapters on the sabbath and the new moon, the sabbatical year an.